Tonographic Effect of Ocular Response Analyzer in Comparison to Goldmann Applanation Tonometry - Zimmermann, Martin; Pitz, Susanne; Schmidtmann, Irene; Pfeiffer, Norbert; Wasielica-Poslednik, Joanna (PloS one, 2017)
The tonographic effect is a phenomenon of intraocular pressure (IOP) reduction following repeated tonometry. This study examines whether the tonographic effect occurs following IOP measurement performed with Ocular Response Analyzer (ORA). Both eyes of 31 glaucoma patients and 35 healthy controls underwent nine IOP-measurements performed with GAT and ORA. The number of GAT and ORA measurements performed on each eye differed depending on the randomly allocated investigation scheme. Central corneal thickness (CCT), anterior chamber volume (ACV) and anterior chamber depth (ACD) were assessed with Pentacam before and after the repeated GAT/ORA measurements. There was no statistically significant tonographic effect for IOP readings obtained by the ORA: corneal compensated intraocular pressure (IOPcc) (-0.11 ± 3.06 mmHg, p = 0.843 in patients and -0.71 ± 3.28 mmHg, p = 0.208 for controls) and Goldmann-correlated intraocular pressure (IOPg) (-0.31 ± 2.38 mmHg, p = 0.469 in patients and -0.31 ± 2.37 mmHg, p = 0.441 in controls) measured with ORA. There was a significant IOP reduction from the first to the second GAT measurement, i.e. tonographic effect (-0.55 ± 2.00 mmHg, p = 0.138 in patients and -1.15 ± 1.52 mmHg, p < 0.001 in controls). CCT, corneal hysteresis (CH) and corneal resistance factor (CRF) were lower in glaucoma patients. The repeated IOP measurements resulted in an increase of CCT in all subjects (but no change of ACV and ACD). The tonographic effect of GAT correlated with CCT in glaucoma patients (r = 0.37). In contrast to GAT, repeated ORA measurements do not result in the tonographic effect. Repeated IOP measurements resulted in an increase of central corneal thickness, but did not influence the volume and depth of anterior chamber.